A plant-based meal reduces postprandial oxidative and dicarbonyl stress in men with diabetes or obesity compared with an energy- and macronutrient-matched conventional meal in a randomized crossover study - Malinska, Hana; Klementová, Marta; Kudlackova, Michaela; Veleba, Jiri; Hoskova, Eva; Oliyarnyk, Olena; Markova, Irena; Thieme, Lenka; Hill, Martin; Pelikanova, Terezie; Kahleova, Hana (Nutrition & metabolism, 2021)
BACKGROUND: Increased oxidative/dicarbonyl stress and chronic inflammation are considered key pathophysiological mediators in the progression of complications in obesity and type 2 diabetes (T2D). Lifestyle and diet composition have a major impact. In this study, we tested the effects of a vegan (V) and a conventional meat containg (M) meal, matched for energy and macronutrients, on postprandial oxidative and dicarbonyl stress, inflammatory markers and appetite hormones. METHODS: A randomised crossover design was used to evaluate T2D, obese with normal glucose tolerance and control participants (n = 20 in each group), with serum concentrations of analytes determined at 0, 120 and 180 min. Repeated-measures ANOVA was used for statistical analysis. RESULTS: In T2D subjects, we observed decreased postprandial concentrations of oxidised glutathione (p ˂ 0.001) and increased glutathione peroxidase activity (p = 0.045) after the V-meal consumption, compared with the M-meal. In obese participants, V-meal consumption increased postprandial concentrations of reduced glutathione (p = 0.041) and decreased methylglyoxal concentrations (p = 0.023). There were no differences in postprandial secretion of TNFα, MCP-1 or ghrelin in T2D or obese men, but we did observe higher postprandial secretion of leptin after the V-meal in T2D men (p = 0.002) compared with the M-meal. CONCLUSIONS: The results show that a plant-based meal is efficient in ameliorating the postprandial oxidative and dicarbonyl stress compared to a conventional energy- and macronutrient-matched meal, indicating the therapeutic potential of plant-based nutrition in improving the progression of complications in T2D and obese patients. Registered under ClinicalTrials.gov Identifier No. NCT02474147.
Keywords: Postprandial state; Inflammation; Type 2 diabetes; Appetite hormones; Oxidative stress; Plant-based diet; Methylglyoxal